The Role of Islamic Leadership in Building Student Character at the Al-Quran-Based SIT Ibnu Moeslim Al-Faqih - Yeni Suryani; Darlina Kartika Rini (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
Leadership plays a strategic role in education, particularly in shaping student character. Amidst the challenges of globalization and the moral crisis gripping society, a leadership model is needed that is not only managerially effective but also capable of instilling noble values, particularly Islamic ones. This study aims to analyze the role of Islamic leadership in building student character at the Quran-based Integrated Islamic School (SIT) Ibnu Moeslim Al-Faqih. Islamic leadership is understood as leadership based on the values ​​of the Quran and Sunnah, with core principles such as khilafah (caliphate), amanah (trust), adl (justice), deliberation (musyawarah), rahmah (compassion), and khidmah (service). Using a qualitative approach with descriptive methods, this study found that Islamic leadership at SIT Ibnu Moeslim Al-Faqih contributes significantly to student character formation through exemplary leadership, the integration of Quranic values ​​into the curriculum and school life, and the creation of an Islamic school culture. The principal acts as a murabbi (leader) and muaddib (leader), ensuring that the entire educational process aligns with Islamic teachings. However, challenges such as limited human resources who fully understand Islamic values ​​remain a challenge. The results indicate that the implementation of Islamic leadership is effective in creating a generation that excels academically, possesses noble character, and is socially responsible.